2008
DOI: 10.1097/mph.0b013e3181812c7c
|View full text |Cite
|
Sign up to set email alerts
|

Focal Nodular Hyperplasia of the Liver and Elevated α Fetoprotein Level in an Infant With Isolated Hemihyperplasia

Abstract: A case of focal nodular hyperplasia of the liver in a 43-day-old baby girl with isolated hemihyperplasia and elevated serum alpha-fetoprotein is presented. The child referred to our hospital with bilateral renal masses detected by prenatal and postnatal ultrasonography. A mass lesion was detected in segment 6 of liver and was diagnosed as focal nodular hyperplasia. We present this case to emphasize the presence of focal nodular hyperplasia in a patient with isolated hemihypertrophy and elevated serum alpha-fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[7] In the literature, high AFP levels in different benign liver masses have been reported. [2][3][4] Sari et al [2] reported elevated AFP levels in a 15-dayold boy with hemangioendothelioma. In this case, initial AFP level was 650 ng/mL (normal range for his age 88±87 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] In the literature, high AFP levels in different benign liver masses have been reported. [2][3][4] Sari et al [2] reported elevated AFP levels in a 15-dayold boy with hemangioendothelioma. In this case, initial AFP level was 650 ng/mL (normal range for his age 88±87 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…The pathologic examination of the specimen revealed mesenchymal hamartoma. [3] The other case was focal nodular hyperplasia of the liver and elevated AFP level in an infant with isolated hemihyperplasia which was reported by Demir et al [4] Herein, we aimed to evaluate the elevated AFP levels in benign/borderline liver masses in this study. There were three boys and two girls with a median age of 6 months (range 1-12 months) at the time that the liver mass was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation